El concepto de orden público internacional y el derecho a un proceso justo. Nota a la STJCE de 2 de abril de 2009 - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
The ECJ should elucidate if, on the base of the clause of public policy established in the article 27.1 CBr, the judge of the addressed State can take into account the fact that the judge of the State of origin has been pronounced on the pretensions of the claimant, without hearing to the defendant that it had duly appeared before him but was excluded of the procedure via a resolution, for not having certain compliment imposed obligations via an adopted resolution previously within the framework of the same procedure.
Keywords: extraterritorial effects of foreign decisions; resolution; international public policy; right to a fair process; rights of defense; right to be been heard